A global perspective of correlation between maternal blood lead levels and risks of preeclampsia: An updated systematic review and meta-analysis - Zhong, Zixing; Yang, Qingmei; Li, Chu; Chen, Xiaohong; Zhou, Feifei (Frontiers in Public Health, 2022)
Background: Preeclampsia (PE) is a hypertensive disorder uniquely developed in pregnancy. Lead is a heavy metal that harms women’s reproductive health. However, it is unclear whether maternal lead exposure may cause preeclampsia during pregnancy. This systematic review and meta-analysis study explored the association between maternal lead exposure and preeclampsia. Methods: We searched studies from three databases (PubMed, Web of Science, Embase). Only case-control, cross-sectional, and cohort studies reporting maternal blood lead levels (BLL) and PE from database inception to 31st Jul 2022 were included. Pregnant women with blood lead levels measured were eligible. Those healthy pregnant women who did not develop preeclampsia were assessed as comparators. Letters, comments, case reports, and reviews were excluded. Newcastle-Ottawa Scale (NOS) and its adaptive form were applied for assessment. The random-effects method (REM) was used for calculating the standard mean difference (SMD) with a 95% confidence interval (CI). Stata 16.0 were the main software used for data extraction and analysis. Results: 25 studies out of 1808 articles made the finalist for systematic reviews, of which 21 reports underwent further quantity analysis. A total of 1533 preeclamptic women and 10998 healthy pregnant controls were included in the meta-analysis. The overall result revealed that maternal lead exposure was significantly higher in women with preeclampsia (SMD: 1.06, 95% CI 0.69, 1.43); (I2 = 96.40%; P = 0.000). Conclusion: This study demonstrates that maternal lead exposure is associated with preeclampsia during pregnancy. The association present even in low blood lead levels. The results should be taken seriously so that women should be advised to avoid unexpected exposure to a lead-containing environment.